First Experiences with Newborn Screening for Congenital Hypothyroidism in Ulaanbaatar, Mongolia - Tsevgee, Altantuya (Int J Neonatal Screen, 2021)
Congenital hypothyroidism (CH) is among the most common conditions leading to intellectual disability, which can be prevented by early detection through newborn screening (NBS). In Mongolia, a regional screening program for CH was launched in 2000, which was supported by the International Atomic Energy Agency (IAEA) for the Asia Pacific Region. In our present study, a total of 23,002 newborns from nine districts in Ulaanbaatar were screened between 2012 and 2020, by the measurement of the thyroid-stimulating hormone (TSH) from dried blood spots, sampled 24 to 72 h after birth. The level of TSH was measured by the DELFIA assay. The overall CH prevalence confirmed at birth was 1/2091. The female-to-male ratio for CH cases was 1.8:1. The majority of patients were asymptomatic (72.7% of CH cases); umbilical hernia and cold or mottled skin were reported symptoms in patients with CH (27.3%). Thyroid dysgenesis (hypoplasia and agenesis) was the most common etiology, with a total of nine cases (81.8%) out of the eleven patients. The lapse between the birth date and the initiation of L-thyroxine treatment in CH-positive children was lower than 15 days in 63.64% of cases or 15 to 30 days in 36.36% of children. Further research is required to expand the screening coverage for CH in Mongolia.